3D printed metamaterials for damping enhancement and vibration isolation: Schwarzites. (15th February 2023) - Herkal, Sudheendra; Rahman, Muhammad M.; Nagarajaiah, Satish; Harikrishnan, Vijay Vedhan Jayanthi; Ajayan, Pulickel
Abstract: Schwarzites are 3D solids with negative Gaussian curvatures that have unusual and interesting mechanical properties. Energy dissipation is one such property Schwarzites offer due to their high ductility and strength. The energy dissipating mechanism can be exploited to remove energy from dynamic systems that have continuous energy input and reduce the system response. Here, the energy dissipation is characterized for 3D printed specimen with solid and Schwarzite geometry. Further, the usefulness of the property is shown by analyzing the reduction in response quantities by performing dynamical simulations. It is found that having Schwarzites geometry increases the damping ratio by nearly 80% with the same amount of material as a solid support. Further, vibration isolation properties of Schwarzites are also illustrated. Highlights: Energy dissipation/vibration isolation of Schwarzite in comparison to solid geometry is studied. Schwarzite offers higher vibration damping ratio than a solid specimen by 80% (on an average). Schwarzite support shifts frequency lower than excitation-resulting in vibration isolation. Vibration isolation and increased energy dissipation result in lower force transmissibility.